2014
DOI: 10.1111/ecc.12232
|View full text |Cite
|
Sign up to set email alerts
|

Returning home: psychosocial care during the re-entry phase of cancer survivorship in rural Australia

Abstract: The purpose of this research was to highlight gaps in formal psychosocial care for cancer survivors in rural communities. The study was conducted in rural Victoria, Australia, and involved interviews with people with various stages of cancer progression, cancer diagnoses and survival times, who were interviewed about their experiences of psychosocial cancer care. Interviews focused on their experience of psychosocial care and were audio-recorded and transcribed verbatim. Data were thematically analysed to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(61 citation statements)
references
References 49 publications
(109 reference statements)
2
59
0
Order By: Relevance
“…Our study highlighted the importance of having formal psychosocial support services in place for the rural cancer patient; many participants (mainly women) reported gaining comfort from such support as the diagnosis of cancer can be “overwhelming.” From our findings it is clear that patients can develop strong relationships with the people who provide them with material and psychological support, and that those supporter's personal qualities and “being there” at a challenging time is very important. Although the psychosocial well‐being of the patients in our study was addressed through the availability of professional psychosocial support (which may be due to their proximity to Bunbury and the reported use of videoconferencing to help with providing support), such support services are not widely available for rural cancer patients, with many psychosocial needs remain unmet (Howard et al., ; Lawler, Spathonis, Masters, Adams, & Eakin, ; Pascal et al., ). The challenges faced by rural health professionals in providing appropriate psychosocial support have also been documented (Breen & O'Connor, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study highlighted the importance of having formal psychosocial support services in place for the rural cancer patient; many participants (mainly women) reported gaining comfort from such support as the diagnosis of cancer can be “overwhelming.” From our findings it is clear that patients can develop strong relationships with the people who provide them with material and psychological support, and that those supporter's personal qualities and “being there” at a challenging time is very important. Although the psychosocial well‐being of the patients in our study was addressed through the availability of professional psychosocial support (which may be due to their proximity to Bunbury and the reported use of videoconferencing to help with providing support), such support services are not widely available for rural cancer patients, with many psychosocial needs remain unmet (Howard et al., ; Lawler, Spathonis, Masters, Adams, & Eakin, ; Pascal et al., ). The challenges faced by rural health professionals in providing appropriate psychosocial support have also been documented (Breen & O'Connor, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, rural cancer survivors can face particular challenges accessing follow‐up care and this has been noted as a particular concern (Howard et al., ; Lawler et al., ; Pascal et al., ). The findings from a study of rural cancer patients in Australia indicated that patients largely cared for themselves during the “re‐entry period” after diagnosis and treatment or received informal support from family and friends (Pascal et al., ). Our study confirmed this weakness and highlighted follow up support as a particular and important gap.…”
Section: Discussionmentioning
confidence: 99%
“…However, successful examples of websites that combine the two are scarce, as are critical reflections on their acceptability and development. This paper makes a unique contribution by demonstrating that working flexibly and utilising both the literature and lived experience to guide the development of resources can foster trust, empower participants, help deliver results that are acceptable to those in both the academic and “real” worlds and help to address what has been described as “a void in formal psychosocial care in rural Australia” (Pascal et al., , p. 48). Although some of the lessons learnt have also been raised via participatory work in other contexts (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it can improve the external validity of research, create space for the expression of local knowledge, build trust and mean resulting programs are more sustainable (Wallerstein & Duran, ). Despite this, “a complete absence of any rural studies that involve people with cancer and their families in service planning” has been highlighted (Pascal et al., , p. 47) and there is “a significant gap in understanding how higher level community participation is best enacted in the rural context” (Kenny et al., , p. 1).…”
mentioning
confidence: 99%
“…A full presentation of the findings is beyond the scope of this article and published elsewhere (Pascal et al . ); hence we have narrowed the specific aims of this article to: Explore the experiences that both facilitate and challenge the receptivity to informal supportive care for people living with and beyond cancer in rural Australia. Develop a Heideggerian analysis in order to understand the central factors influencing receptivity to informal supportive care. …”
Section: Introductionmentioning
confidence: 99%